FES null mice demonstrate a reduction in neutrophil dependent pancreatic cancer metastatic burden - Strøbech, Jan E.; Giuriatti, Pietro; Stagaard, Rikke; De Sepulveda, Paulo; Nielsen, Sebastian R.; Erler, Janine T. (Frontiers in Oncology, 2023)
Patients with pancreatic ductal adenocarcinoma (PDAC) have a dismal 5-year survival rate of less than 10%, predominantly due to delayed diagnosis and a lack of effective treatment options. In the PDAC tumor microenvironment (TME), neutrophils are among the immune cell types that are most prevalent and are linked to a poor clinical prognosis. However, treatments that target tumor-associated neutrophils are limited despite recent developments in our understanding of neutrophil function in cancer. The feline sarcoma oncogene (FES) is a nonreceptor tyrosine kinase previously associated with leukemia and hematopoietic homeostasis. Here we describe a newly derived FES null mouse with no distinct phenotype and no defects in hematopoietic homeostasis including neutrophil viability. The immune cell composition and neutrophil population were analyzed with flow cytometry, colony-forming unit (CFU) assay, and a neutrophil viability assay, while the response to PDAC was examined with an in vivo cancer model. In an experimental metastasis model, the FES null model displayed a reduced PDAC hepatic metastatic burden and a reduction in neutrophil granulocytes. Accordingly, our results indicate FES as a potential target for PDAC TME modulation.